Internalisation of Islamic Religious Education Values through Best Practice Programmes - Syifa Nur Salsabila; Satriyadi (The Islamic Education and Multiculturalism Foundation, 2025)
Islamic Religious Education (PAI) is an educational discipline that aims to cultivate students' spiritual, moral, and character development. To this end, numerous educational institutions (madrasas) have effectively implemented character education programs, utilizing models that they have developed autonomously. This particular madrasa exemplifies the optimal approach to character education through religious instruction in Indonesia. The objective of this study is to investigate the efficacy of Islamic religious education at Mas Du Al Muhajirin Padang Cermin. The present study employs a qualitative approach. The data was collected through a combination of interviews, group discussions (focus group discussions), observations, and documentation. The results indicated that the role of the madrasa head was found to be of significant importance in the continuity and support of the development of religious activities in the madrasa. Furthermore, the PAI teacher was identified as a central figure in the success of the religious development and the style of student religious thinking. Additionally, the role of the Rohis position was determined to be very strategic in developing the younger generation who had moderate, tolerant, and Islam rahmatan lil alamin beliefs. The implementation of tadarus at the commencement of each lesson, the duha prayer, congregational prayer, the implementation of PHBI, cult after congregational prayers, cultrian, pesantren kilat, and mentoring became a reinforcement or standard in the implementation of religious activities in madrasas.